2018
DOI: 10.3390/sym10080333
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Level Privacy-Preserving Approach to Hierarchical Data Based on Fuzzy Set Theory

Abstract: Nowadays, more and more applications are dependent on storage and management of semi-structured information. For scientific research and knowledge-based decision-making, such data often needs to be published, e.g., medical data is released to implement a computer-assisted clinical decision support system. Since this data contains individuals’ privacy, they must be appropriately anonymized before to be released. However, the existing anonymization method based on l-diversity for hierarchical data may cause a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Otherwise, Wang et al [10] suggested a multilevel privacy-preserving approach based on fuzzy sets to ensure privacy. e proposed algorithm treats both numerical and categorical sensitive attributes by converting the categorical attribute value into a numerical attribute value based on its occurrence frequency.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Otherwise, Wang et al [10] suggested a multilevel privacy-preserving approach based on fuzzy sets to ensure privacy. e proposed algorithm treats both numerical and categorical sensitive attributes by converting the categorical attribute value into a numerical attribute value based on its occurrence frequency.…”
Section: Related Workmentioning
confidence: 99%
“…e proposed algorithm treats both numerical and categorical sensitive attributes by converting the categorical attribute value into a numerical attribute value based on its occurrence frequency. Unlike the previous algorithms, the suggested one in [10] can resist the similarity attack by partitioning sensitive values into five levels and then setting a sensitivity level for each sensitive value. Based on semantic rules, Mubark et al [39] proposed a technique dealing with categorical data.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations